Limit on Reduction of the Power Load to Target Plates for DEMO Reactor. Issue 4 (June 2014) - Stankiewicz, R.; Stępniewski, W.
Abstract The several Demo design concepts have been analyzed using the code Corediv solving self consistently the core and scrape off layer regions. The numerical analyses show that there exists the limit on the concentration of impurities above which the solution with burning plasma does not exists. This limits reduce the possibility of reduction of power loads to target plate. In the paper the admissible range of seeded impurity concentration introduced to reduce the power load to divertor plate is analyzed. The possible mechanisms leading to the limitation are shown. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)